Disrupted Learning: The Impact of Terror Attacks on Beninese EFL Learners’ Motivation in some Secondary Schools of Northern Region - KOTTIN, Assogba Evariste (My University, 2024)
Terrorist threats continue to pose a significant challenge to global security, especially in Benin. This can be shown by a report of Institute Security Studies in 2023 on "violent extremism" in northern Benin, primarily from extremist groups operating in neighboring countries like Burkina Faso where "more than 3,000 schools" are forced to be closed, reported by Aurore, B. (2022). This research aims to investigate the impact of terrorist threats on English as a Foreign Language (EFL) learner’s motivation in Benin. It seeks to explore the extent to which terror attacks affected the teachinglearning process, the effectiveness of EFL teachers, and the experiences of students in English learning. The study will also examine the strategies employed by teachers to cope with the challenges posed by threats and their implications for EFL education in Benin. To that effect, data have been collected through the quantitative and qualitative analysis techniques, including interviews and questionnaires addressed to 52 EFL teachers and 615 EFL learners. The findings of this study reveal that terrorist attacks have had a significant negative impact on EFL learners’ motivation and EFL instructions are badly affected. It can be suggested that peace education be integrated into the educational system to mitigate the negative impact of violence on EFL teaching and learning in the country.
Keywords: Terror Attacks; Teaching; Learning; Peace; EFL